Relationship between job satisfaction, emotional intelligence, motivation and organizational commitment among secondary school teachers in Tambunan district - Nur Afny Juati; Mohamad Nizam Nazarudin; Nur Afny Juati; Jumadi Musa; Hujaimah @ Siti Syafiqah Juhumin (Global Academic Excellence, 2020)
School teachers need organizational commitment so that they can contribute their services, efforts, and energy to the organization. This study aimed to examine the relationship between job satisfaction, emotional intelligence, motivation, and organizational commitment among secondary school teachers in Tambunan District. A total of 175 teachers from four secondary schools were involved in this study. The questionnaire containing 97 items of five Likert scales was used to measure respondents' responses. Statistical methods Pearson correlation, t-test, and one-way analysis of variance (ANOVA) were used. The results showed that a) there was no difference in job satisfaction, emotional intelligence, and gender-based motivation, b) there was no difference in job satisfaction based on the duration of service and there were differences in emotional and motivational intelligence based on service duration and c) there was a significant relationship between job satisfaction, intelligence emotions and motivation with organizational commitment. Based on this finding, teachers need to have high levels of work satisfaction, emotional intelligence, motivation, and commitment to remain in a stable state and thus develop students' potential through effective teaching and learning.